Mechanism of information resources knowledge - A. M. Izmailov (Vestnik Voronežskogo Gosudarstvennogo Universiteta Inženernyh Tehnologij, 2016)
Modern vector of development of the economy is quite different from previous periods, which in it turn is reflected in the strategic state documents generated including the Government of Russia. In particular, it should be noted that to date, the state defined the vector of development defined as an innovative and socially oriented. Given the level of technical and technological progress and its impact on the realities of the present time it is necessary to pay attention to enhance the relevance and significance of information in the development of modern society. The article analyzes the degree of influence of information and knowledge in modern economic processes taking place in society. The analysis is based on the study of scientific works of modern scientists specializing in the study of information problems and knowledge economy. The main trends in the development of the information society status related primarily to the expansion of data, as well as strengthening the role of progressive information technologies to reduce the role of the geographical factor of resistance in sharing knowledge. The authors defined the essence of information knowledge environment, as well as the marked characteristics form the spectrum of features inherent to the modern information environment. The analysis of the concept of «information knowledge resource» (IKR), which is a synthesis of three terms: information, knowledge, resources, and refined his interpretation. IKR designated role in shaping the knowledge economy. Presents specific features which have knowledge information and resources, among which stands out: intangibility, immeasurable, non-exclusive use. The paper presents a model of the PSI, based on the transformation of information into knowledge under the influence of certain factors that could affect the quality of the resulting knowledge. Also in the proposed IKR management mechanism as a central element of organizational change management mechanisms in the social and economic systems. Outlined the main points useful application of such a mechanism.